Analysis on Administrative Services in Dental Poly Clinic PLK Unair 2017 - Jaqueline Kerina (Universitas Airlangga, 2018)
Service delivery and healthcare have become trends. Pusat Layanan Kesehatan Universitas Airlangga (PLK UNAIR) is in a network with various hospitals and governmental health insurance agencies for the community. The objective of this study is to describe the flow of the administrative services in the dental unit of PLK UNAIR. This study used a qualitative design through active participation, interviews, and observations. Results drawn from this study showed that the flow of administrative services at PLK UNAIR was successfully carried based on its objectives through the contribution of its employees. The summary shows the identification of patient flow at PLK UNAIR dental unit results in the high influx of patients which are mostly students. Keywords: administration, patients, services and students.